Implementation of Child Offenders of Narcotics and Psychotropic Crimes at the Madiun District Court - Saputra, Raka Kencana (JOSAR (Journal of Students Academic Research), 2024)
This study discusses the implementation of child perpetrators of narcotics and psychotropic crimes at the Madiun District Court. The choice of topic and background in this study was based on the fact that narcotics abuse has long been a serious problem in various countries, especially in Indonesia. An example of the adverse effects that have occurred in Indonesia, especially for the wider community, is the adverse impact of friendships which often have a negative influence on children. nation. One example is drug abuse. With its legal basis, namely Law number 5 of 1997 concerning psychotropics and Law number 22 of 1997 concerning Narcotics which was later updated to become Law number 35 of 2009 concerning narcotics, Then for criminal sanctions against children who commit basic crimes the law is Law Number 23 of 2002. In the Implementation of Child Offenders of Narcotics and Psychotropic Crimes at the Madiun District Court. The method used is empirical juridical research which is legal research involving various supports from the community or outside parties in accordance with existing law, involving the community or the surrounding environment based on social science. The analysis used is qualitative analysis using interviews, as well as literature studies. Sourced from this method, it can be described the implementation of child perpetrators of narcotics and psychotropic crimes at the Madiun District Court.